Health Consequences of Sarcopenic Obesity: A Narrative Review - Roh, Eun; Choi, Kyung Mook (Frontiers in Endocrinology, 2020)
Sarcopenia is defined as the age-related loss of muscle mass and strength or physical performance. Increased amounts of adipose tissue often accompany sarcopenia, a condition referred to as sarcopenic obesity. The prevalence of sarcopenic obesity among adults is rapidly increasing worldwide. However, the lack of a universal definition of sarcopenia limits comparisons between studies. Sarcopenia and obesity have similar pathophysiologic factors, including lifestyle behaviors, hormones, and immunological factors, all of which may synergistically affect the risk of developing a series of adverse health issues. Increasing evidence has shown that sarcopenic obesity is associated with accelerated functional decline and increased risks of cardiometabolic diseases and mortality. Therefore, the identification of sarcopenic obesity may be critical for clinicians in aging societies. In this review, we discuss the effect of sarcopenic obesity on multiple health outcomes and its role as a predictor of these outcomes based on the components of sarcopenia, including muscle mass, muscle strength, and physical performance.